2019
DOI: 10.4236/jqis.2019.93008
|View full text |Cite
|
Sign up to set email alerts
|

The Wave-Particle Duality—Does the Concept of Particle Make Sense in Quantum Mechanics? Should We Ask the Second Quantization?

Abstract: The quantum object is in general considered as displaying both wave and particle nature. By particle is understood an item localized in a very small volume of the space, and which cannot be simultaneously in two disjoint regions of the space. By wave, to the contrary, is understood a distributed item, occupying in some cases two or more disjoint regions of the space. The quantum formalism did not explain until today the so-called "collapse" of the wave-function, i.e. the shrinking of the wavefunction to one sm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Vis-à-vis this claim, Section 3 of [35] presents a contradiction between the dBB mechanics and QM, reasoning within one single frame of coordinates. Its main line is described below.…”
Section: The De Broglie-bohm Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vis-à-vis this claim, Section 3 of [35] presents a contradiction between the dBB mechanics and QM, reasoning within one single frame of coordinates. Its main line is described below.…”
Section: The De Broglie-bohm Interpretationmentioning
confidence: 99%
“…The relevant trials of the experiment are those in which all the three detectors D 1 , D 2 , and D 3 , click. The calculi in [35] showed that for the phase-shifts 1) The w-p a triggers the detector D 1 , and the detectors D 2 and D 3 are triggered by the oscillators; Figure 2. An arrangement for simultaneous detections of one particle in different places.…”
Section: The De Broglie-bohm Interpretationmentioning
confidence: 99%
“…The de Broglie-Bohm interpretation of QM is based on the assumption of particles floating inside the wave-function and following continuous trajectories. The existence of such continuous trajectories was disproved in [5] Section 3.…”
Section: The Transactional Interpretationmentioning
confidence: 99%
“…If the w-f consists of several w-ps, the particle travels with one of them, and the rest of the w-ps are considered some sort of really existing waves, though to which the detectors are insensitive. However, a strong argument was brought against the dBB mechanics in [18]. 2 What was challenged in [18] wasn't the existence of a particle as a substructure of the QM formalism.…”
Section: Introductionmentioning
confidence: 99%
“…However, a strong argument was brought against the dBB mechanics in [18]. 2 What was challenged in [18] wasn't the existence of a particle as a substructure of the QM formalism. The possibility of a continuous trajectory for the alleged particle was proved incompatible with the QM predictions.…”
Section: Introductionmentioning
confidence: 99%